1998
DOI: 10.1023/a:1022538530701
|View full text |Cite
|
Sign up to set email alerts
|

H2-Uptake Activity, Spectra, Reduction Potentials, and Kinetics of Iron Release on the Surface of Iron Core from Azotobacter vinelandii Bacterial Ferritin

Abstract: Bacterial ferritin from Azotobacter vinelandii (AvBFo) has a function in H2 uptake. The Fe3+ reduction on the surface of the iron core from AvBFo is accompanied simultaneously by H2 uptake, with a maximum activity of H2 uptake of 450 H2/AvBFo. A reduction potential of -402 mV for iron reduction on the surface of the core is found. A shift to the red the protein absorbance peaks ranging from 280 to 290 nm is observed between pH 5 and 9 under 100% H2 reduction. The reduction potential for iron release becomes ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Research has also been carried out at fundamental level to study the influence of hydrogen on the combustion characteristics of methane. The enrichment of methane with hydrogen has been observed to increase the laminar burning velocity [16][17][18][19] and reduce the igni tion delay time [20] and laminar flame thickness as well as the dependence of the laminar burning velocity on the flame stretch [21]. The increase of laminar burning velocity with hydrogen addition is attributed to the flooding o f the reaction zone with H, O, and OH radicals that have strong positive correlation with the burning velocity [1, 22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also been carried out at fundamental level to study the influence of hydrogen on the combustion characteristics of methane. The enrichment of methane with hydrogen has been observed to increase the laminar burning velocity [16][17][18][19] and reduce the igni tion delay time [20] and laminar flame thickness as well as the dependence of the laminar burning velocity on the flame stretch [21]. The increase of laminar burning velocity with hydrogen addition is attributed to the flooding o f the reaction zone with H, O, and OH radicals that have strong positive correlation with the burning velocity [1, 22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Huang and his colleagues found that Fe 3+ can be reduced on the surface of apoferritin iron core, and the release kinetics of iron on the core surface is a first-order reaction. 64 This iron release process is affected by external factors or active components. Therefore, research on regulating the reductive release of ferritin is beneficial to promoting the application of ferritin as an iron supplement.…”
Section: Ferritin Functions In Transporting Mineralsmentioning
confidence: 99%
“…From the release kinetics curve, two consecutive first-order reactions (a reaction in which the reaction rate is directly proportional to the concentration of the reactant) were observed, and the experimental results indicated that heme played an electron transfer role in the reduction release of Azobacter ferritin. Huang and his colleagues found that Fe 3+ can be reduced on the surface of apoferritin iron core, and the release kinetics of iron on the core surface is a first-order reaction …”
Section: Ferritin Functions In Transporting Mineralsmentioning
confidence: 99%